Clinical use of Cymbopogon citratus stapf products in bucal pathologies: integration review - Viana, Maria Augusta Correa Barroso Magno (2021)
This work aims to present an integrative review on the potential of Cymbopogon citratus (DC.) Stapf on candidiasis in the oral cavity. Articles published in the LILACS, MEDLINE/PUBMED databases were selected, using the descriptors: Cymbopogon, Candida and oral candidiasis. Studies that were related to the purpose of the review and the presence of the aforementioned descriptors in the title, abstract and body of the text were included in Portuguese and or English. The selection of articles resulted in 67 studies, of which 16 were selected to compose the manuscript, which demonstrated the ways of using C. citratus and its action in the treatment of oral candidiasis. It was possible to demonstrate the effectiveness of using C. citratus to treat infections of the genus Candida that affect the oral cavity, mainly as a complement to conventional treatment. However, caution is required when prescribing use, since most studies were carried out in laboratories and have not been tested in vivo. It is concluded that both the essential oil and the extract of C. citratus have antifungal action against the genus Candida, although some studies show cytotoxicity and mutagenicity, which must be considered for the safety of its use.